The Effect of Economic Growth, HDI, District/City Minimum Wage and Unemployment on Inequity of Income Distribution in Province of D.I Yogyakarta (2010-2018) - Krisna Gita Suryani; Nenik Woyanti (Media Ekonomi dan Manajemen, 2021)
The high inequality of income distribution that occurs in the Special Region of Yogyakarta Province shows that economic development has not succeeded in bringing equity to the community. For this reason, an analysis is needed to determine the factors that inequality of income distribution in order to reduce inequality of income distribution that occurs in the Province of DI Yogyakarta. The purpose of this study was to determine the effect of economic growth, HDI, Distric/City Minimum Wage, and Unemployment. This research uses secondary data obtained from the Central Statistics Agency of D.I Yogyakarta Province. The data in this research is panel data consisting of cross section data from 5 districs/cities and time series data for 2010-2018. The data analysis used was panel data regression analysis with the Fixed Effect regression model. The results of the regression analysis show that economic growth does not have a significant effect on inequality of income distribution. Meanwhile, HDI, Distric/City Minimum Wages and Unemployment have a significant effect on the inequality of income distribution. HDI has a negative effect, while Distric/City Minimum Wage and Unemployment have a positive effect on inequality of income distributed in the Province of DI Yogyakarta in 2010-2018